PENGARUH PERSEPSI KEMIRIPAN, KONSEP MEREK DAN PESAN IKLAN TERHADAP RESPON KONSUMEN DALAM MENGEVALUASI PERLUASAN MEREK - Arini Ekaputri Junaedi (Jurnal Ekonomi dan Bisnis Airlangga, 2017)
Introduction: This study aims to determine the effect of product category similarity when associated with brand concepts and advertising messages on consumer responses in evaluating brand expansion. To get the research objective, two studies were conducted sequentially.Methods: The first study used experiments conducted on the similarity category of the product and the brand concept. The second study uses experiments conducted on product similarity categories and advertising messages. Experiments in both studies were carried out using the between-subject method with 240 undergraduate students at the Faculty of Economics and Business, Airlangga University (120 students for each study) as participants.Results: The experimental results from the first study show that the prestigious brand concept has a better ability (compared to the functional brand concept) to carry out brand expansion both in product categories that are similar or not similar to the original brand. The experimental results from the second stage study show that a prestigious brand will be able to increase its ability to expand the brand if the product is advertised with a social-adjustive message for similar product categories, and for dissimilar product categories it will be more effective if advertised with a value-expressive message.Conclusion and suggestion: Companies that do brand extensions to different product categories are advised to use ads with value-expressive messages to make them more effective.